2010
DOI: 10.1111/j.2042-3306.2010.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography activity of the equine splenius muscle and neck kinematics during walk and trot on the treadmill

Abstract: SummaryReasons for performing study: Skeletal muscle activity can be concentric or eccentric, anisometric or isometric and correlation of the equine splenius muscle activity with the movement of its effector joints at walk and trot has not yet been fully characterised. Objective: Investigating activity of the splenius muscle together with kinematics of head and cranial neck at walk and trot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…In contrast, Zsoldos et al. () found significant differences between the right and the left m. splenius, but we could not confirm these findings in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, Zsoldos et al. () found significant differences between the right and the left m. splenius, but we could not confirm these findings in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our measurements were made over ground, not by using a treadmill (as Zsoldos et al. () did), because between these two forms of locomotion are only minor differences (Gomez Álvarez et al., ) and normal horses are used to walk over ground.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo electromyography of the cervical musculature of walking horses showed that the splenius muscle exhibits bilateral activity during the single support stance of each forelimb [37][38][39], that is when head and neck reach the lowest position. It would seem that the activity pattern of this main dorsal muscle of the cervical spine is enough to induce the observed vertical motion of the head-neck unit.…”
Section: Discussionmentioning
confidence: 99%